Respuesta :

[tex]\bold{Answer}[/tex]

[tex]\boxed{\bold{Y \ = \ 1, \ X \ = \ 5}}[/tex]

[tex]\bold{Explanation}[/tex]

  • [tex]\bold{Use \ Elimination \ Method: \ \begin{bmatrix}x+y=6\\ x-y=4\end{bmatrix}}[/tex]

[tex]\bold{----------------}[/tex]

  • [tex]\bold{Isolate \ x \ for \ x+y=6: \ x=6-y}[/tex]

[tex]\bold{Substitute \ X \ = \ 6 \ - \ y}[/tex]

[tex]\bold{\begin{bmatrix}6-y-y=4\end{bmatrix}}[/tex]

  • [tex]\bold{isolate \ y \ for \ 6-y-y=4: \ Y \ = \ 1}[/tex]

[tex]\bold{For \ x=6-y}[/tex]

[tex]\bold{Substitute \ y \ = \ 1}[/tex]

[tex]\bold{6-1=5}[/tex]

[tex]\bold{x=5}[/tex]

[tex]\boxed{\bold{Eclipsed}}[/tex]

Answer:

5,1

Step-by-step explanation:

a.p.e.x